FRI0020 Blocking the inhibitory CD94/NKG2A NK cell receptor with a novel ANTI-NKG2A MAB enhances the susceptibility of rheumatoid arthritis fibroblast-like synoviocytes (FLS) to NK cell-mediated cytotoxicity. (23rd January 2014) - Nielsen, N.; Galsgaard, E.D.; Ahern, D.; Andersen, M.; Spee, P.; Feldmann, M.; Brennan, F.; Söderström, K.
Abstract : Background: Rheumatoid arthritis (RA) is an autoimmune disease characterized by chronic inflammation and synovial hyperplasia leading to progressive bone erosion and cartilage degradation [1]. Fibroblast-like synoviocytes (FLS) present in the inflamed joints of RA patients are central components of the aggressive, tumor-like structure named pannus that erodes the joints [2]. CD94/NKG2A+ natural killer (NK) cells are found in the inflamed joints of RA patients [3], and their role in the disease process is emerging. Objectives: The aims of the present study were to characterize the expression of potential ligands for NK cell receptors on rheumatoid arthritis synovial tissue-derived FLS, investigate the susceptibility of FLS to NK cell-mediated lysis in vitro, as well as characterize, phenotype and localize NK cells and FLS in inflamed RA joints. Methods: FLS were derived from human synovial tissue obtained from the small joints of RA patients undergoing arthroscopic synovectomy. NK cells from the blood of healthy donors, or the synovial fluid of RA patients, were co-cultured with FLS, and the susceptibility of FLS to NK cell-mediated cytotoxicity was assessed by degranulation of NK cells and subsequent expression of CD107a/b by flow cytometry. Flow cytometry was performed on FLS and NK cells to characterize the expression of NK cell ligands and receptors, respectively. Results: RA synovial NK cells express several activating receptors of which primarily NKG2D, DNAM-1 and NKp44 are involved in killing of FLS upon co-culture in vitro. Furthermore, FLS express numerous ligands for such activating NK cell receptors, and also express HLA-E, a molecule responsible for restraining NK cell-mediated cytotoxicity through interactions with CD94/NKG2A inhibitory receptors expressed on most synovial NK cells. We found that blocking the interaction between HLA-E and CD94/NKG2A with a novel humanized anti-NKG2A mAb (NNC141-0100) enhanced NK cell degranulation towards FLS. Conclusions: This study is the first to suggest that NK cells may play a role in the elimination of FLS, a process that is enhanced upon blocking the ability of HLA-E to engage the inhibitory CD94/NKG2A NK cell receptor. Exploitation of the cytotoxic potential of NK cells by blocking CD94/NKG2A with the novel humanized anti-NKG2A mAb NNC141-0100 may thus yield an opportunity for therapeutic treatment of chronic inflammation. NNC141-0100 is currently being tested in a phase I clinical trial for rheumatoid arthritis. References: Gerlag DM et al. Novel approaches for the treatment of rheumatoid arthritis: lessons from the evaluation of synovial biomarkers in clinical trials. Best Pract Res Clin Rheumatol. 2008 Apr;22(2):311-23. Neumann E et al. Rheumatoid arthritis progression mediated by activated synovial fibroblasts. Trends Mol Med. 2010 Oct;16(10):458-68. Teixeira de Matos C et al. Activating and inhibitory receptors on synovial fluid natural killer cells of arthritis patients: role of CD94/NKG2A in control of cytokine secretion. Immunology. 2007 Oct;122(2):291-301. Disclosure of Interest: N. Nielsen Shareholder of: Novo Nordisk, Employee of: Novo Nordisk, E. Galsgaard Shareholder of: Novo Nordisk, Employee of: Novo Nordisk, D. Ahern: None Declared, M. Andersen Employee of: Novo Nordisk, P. Spee Shareholder of: Novo Nordisk, M. Feldmann: None Declared, F. Brennan: None Declared, K. Söderström Employee of: Novo Nordisk